2009
DOI: 10.1097/sle.0b013e31818e91f3
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic Colectomy

Abstract: The use of a medial approach in a laparoscopic colectomy provides short-term benefits compared with a lateral approach.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(16 citation statements)
references
References 25 publications
0
16
0
Order By: Relevance
“…The operative approach of CME includes lateral or medial access. According to the literature, lateral access or medial access is used to conduct CME procedures [ 24 25 ]. For right hemicolectomies, lateral access is usually performed in most open surgeries, whereas medial access is used in most laparoscopic approaches.…”
Section: Discussionmentioning
confidence: 99%
“…The operative approach of CME includes lateral or medial access. According to the literature, lateral access or medial access is used to conduct CME procedures [ 24 25 ]. For right hemicolectomies, lateral access is usually performed in most open surgeries, whereas medial access is used in most laparoscopic approaches.…”
Section: Discussionmentioning
confidence: 99%
“…The authors encouraged the use of MA for patients requiring a laparoscopic right hemicolectomy. Rotholtz et al [ 6 ] reported that the MA significantly reduced the operation time and time to intestinal recovery. Yan et al [ 11 ] published results showing that the MA resulted in a shorter operative time and less blood loss in laparoscopic right hemicolectomy.…”
Section: Discussionmentioning
confidence: 99%
“…Our study revealed a significantly shorter operative time and less blood loss in the MA group. Possible reasons for this were as follows: a).with the MA, it was easy for the surgeon to keep the dissection at the bloodless plane between the mesocolon and the retroperitoneum and to reduce blood loss accordingly[ 6 ];b).less amount of bleeding was expected with MA during mobilization of the colon when ligating the vessels primarily[ 11 ]; c).in some rare conditions in which the colonic tumor coexists with a colonic inflammatory process (e.g., diverticulitis),the LA might be difficult and dangerous because the LA is blurred during the divisions[ 19 ]. Our results of operative time and blood loss are in agreement with reported operation times in published studies.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations